Analisis Dan Sistem Pengendalian Persediaan Bahan Baku Dalam Meningkatkan Efisiensi Biaya - Favian Jiwani; Sajiyo Sajiyo (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze and propose improvements to the raw material inventory control system in a public street lighting pole manufacturing company. The problem faced by the company is that the inventory control system is still managed in a simple and non-integrated manner, resulting in delays in raw material procurement, discrepancies in inventory quantities, and increased operational costs that disrupt the smooth production process. This research uses the Material Requirement Planning (MRP) method as the main approach in planning raw material requirements. The research stages include collecting data on product demand, production data, raw material usage, inventory levels, ordering costs, holding costs, and procurement lead times. Demand data are analyzed using forecasting methods to estimate future production requirements, followed by material requirement calculations based on the Bill of Materials (BOM) and production planning. Furthermore, MRP analysis is conducted along with the implementation of lot sizing methods such as Lot for Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) to determine the optimal order quantity. The results of this study are expected to produce a more planned, effective, and efficient raw material inventory control system, enabling the company to minimize the risk of shortages and excess inventory, reduce inventory costs, improve the smoothness of the production process, and enhance the company’s ability to fulfill customer demand on time. Keywords: Cost Efficiency; Inventory Control; Material Requirement Planning (MRP); Production Planning; Raw Materials. Penelitian ini bertujuan untuk menganalisis serta memberikan usulan perbaikan terhadap sistem pengendalian persediaan bahan baku pada perusahaan manufaktur tiang Penerangan Jalan Umum. Permasalahan yang dihadapi perusahaan adalah sistem pengendalian persediaan yang masih dilakukan secara sederhana dan belum terintegrasi, sehingga sering terjadi keterlambatan pengadaan bahan baku, ketidaksesuaian jumlah persediaan, serta meningkatnya biaya operasional yang berdampak pada terganggunya kelancaran proses produksi. Penelitian ini menggunakan metode Material Requirement Planning (MRP) sebagai pendekatan utama dalam perencanaan kebutuhan bahan baku. Tahapan penelitian meliputi pengumpulan data permintaan produk, data produksi, penggunaan bahan baku, persediaan, biaya pemesanan, biaya penyimpanan, serta lead time pengadaan. Data permintaan dianalisis menggunakan metode peramalan untuk menentukan estimasi kebutuhan produksi di masa mendatang, kemudian dilakukan perhitungan kebutuhan material berdasarkan Bill of Materials (BOM) dan perencanaan produksi. Selanjutnya dilakukan analisis MRP serta penerapan metode lot sizing Lot for Lot (LFL), Economic Order Quantity (EOQ), dan Period Order Quantity (POQ) untuk menentukan jumlah pemesanan yang optimal. Hasil penelitian diharapkan mampu menghasilkan sistem pengendalian persediaan bahan baku yang lebih terencana, efektif, dan efisien, sehingga perusahaan dapat meminimalkan risiko kekurangan maupun kelebihan persediaan, menekan biaya persediaan, serta meningkatkan kelancaran proses produksi dan kemampuan perusahaan dalam memenuhi permintaan pelanggan secara tepat waktu. Kata kunci: Bahan Baku; Efisiensi Biaya; Material Requirement Planning (MRP); Pengendalian Persediaan; Perencanaan Produksi.